1987
DOI: 10.1083/jcb.105.6.2915
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of acyl-CoA oxidase into peroxisomes requires ATP hydrolysis but not a membrane potential.

Abstract: Abstract. An efficient system for the import of newly synthesized proteins into highly purified rat liver peroxisomes was reconstituted in vitro. 35S-Labeled acyl-CoA oxidase (AOx) was incorporated into peroxisomes in a proteinase K-resistant fashion. This import was specific (did not occur with mitochondria) and was dependent on temperature, time, and peroxisome concentration. Under optimal conditions •30% of T hE biogenesis ofperoxisomes has unique features that distinguish it from the assembly of other orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
112
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 187 publications
(118 citation statements)
references
References 43 publications
4
112
2
Order By: Relevance
“…All assays are in accord that peroxisomes do not import substrates at low temperatures ( [16,18,20], Figs. 3 and 4B).…”
Section: Figmentioning
confidence: 82%
See 4 more Smart Citations
“…All assays are in accord that peroxisomes do not import substrates at low temperatures ( [16,18,20], Figs. 3 and 4B).…”
Section: Figmentioning
confidence: 82%
“…Import appeared to peak at approximately 45 min-roughly consistent with the time course results obtained with other import assays. That is, Wendland and Subramani [20], using the immunofluorescence-based import assay, and Walton et al [4], using the microinjection-based import assay, observed maximal import at 1 h; Imanaka et al [16], using purified rat liver peroxisomes, observed a plateau at approximately 30 min.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations